Simulation and Arduino Hardware Implementation of DC Motor Control Using Sliding Mode Controller - Alfian Ma'arif; Abdullah Çakan (Universitas Muhammadiyah Yogyakarta, 2021)
The research proposed an alternative controller to control the Direct Current (DC) Motor using a sliding mode controller (SMC) in Matlab Simulink simulation and Arduino hardware implementation. The proposed controller, SMC, was designed using the system model (equivalent control) and Lyapunov control design (also to prove the stability). The sliding mode controller had a better response than PID Controller, with no overshoot response in the simulation result. In the Arduino hardware implementation result, the augmented system could reach the reference but has an oscillation and chattering effect in the control signal. The chattering could be reduced by modifying the switching control. Comparing with PID, SMC had a better response with no overshoot. Thus, the SMC could be used as an alternative controller for the DC Motor.